2021
DOI: 10.31234/osf.io/es3rd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pandemic Grief in Poland: Adaptation of a Measure and its relationship with Social Support and Resilience

Abstract: Millions of people are mourning the death of a loved to COVID-19. According to previous studies, the circumstances of coronavirus disease-related deaths may lead to dysfunctional grief. The purpose of this study was to introduce the Polish adaptation of the Pandemic Grief Scale (PGS) as well as to assess the relationship between dysfunctional grief due to a COVID-19 death, resilience and perceived social support. The adaptation was carried out on a general population sample of 286 individuals aged 18–54 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Students mainly expressed a need for emotional, organizational, and psychological support from their families and friends in order to maintain a high level of functioning, which might be explained through the perspective of the resilience theory [71,72]. This is because resilience is strongly related to, among others, perceived emotional support and close, safe relationships with one's family and friends [73,74], which create networks of emotional and social support [75,76]. The ability to use support serves as a buffer for stress and its negative consequences.…”
Section: Plos Onementioning
confidence: 99%
“…Students mainly expressed a need for emotional, organizational, and psychological support from their families and friends in order to maintain a high level of functioning, which might be explained through the perspective of the resilience theory [71,72]. This is because resilience is strongly related to, among others, perceived emotional support and close, safe relationships with one's family and friends [73,74], which create networks of emotional and social support [75,76]. The ability to use support serves as a buffer for stress and its negative consequences.…”
Section: Plos Onementioning
confidence: 99%
“…It should be noted that, according to recent reports, resilience is a significant predictor of mental health behavior during the COVID-19 pandemic [34]. Researchers indicate that resilience may, inter alia, reduce the symptoms of post-traumatic stress, anxiety about the coronavirus, and the intensification of complicated grief in people who could not take care of their relatives' final arrangements during the lockdown [35,36]. Researchers also found that the average immunity in the population during the outbreak was lower than published standards, but was higher among those who went outside more often, exercised more, had greater social support from family, friends, and other important people, slept better, and prayed more [37,38].…”
Section: Of 12mentioning
confidence: 99%
“…This study adds to an emerging body of work on how social support relates to well-being during the COVID-19 pandemic. Perceived social support is associated with decreased anxiety during the pandemic (Özmete & Park, 2020), decreased dysfunctional grief over COVID-19 related death (Skalski et al, 2021), decreased depression related to pandemic-era racial discrimination (Lee & Waters, 2021), and decreased depression, anxiety, and loneliness during quarantine (Grey et al, 2020). Expanding on this work, the current study suggests that the perceived freedom to choose relationships may modulate such effects: people higher in relational mobility received more social support from new friends during the pandemic, compared to people lower in relational mobility, and this was linked to higher well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship quality also matters for well-being under crisis circumstances (Cobb, 1976), because relationship partners are important sources of social and emotional support in times of need (Lakey & Orehek, 2011; Ognibene & Collins, 1998). The amount of social support that people receive, or expect to receive, from others is associated with decreased psychological and somatic symptoms both on and after stressful days (Delongis et al, 1988), less emotional distress and better work adjustment after hospitalization (Porritt, 1979), fewer psychological and behavioral symptoms of stress after a nuclear accident (Fleming et al, 1982), and decreased anxiety and depressive symptoms during the COVID-19 pandemic (Grey et al, 2020; Lee & Waters, 2021; Özmete & Park, 2020; Skalski et al, 2021).…”
Section: Relationship Quality Is Associated With Well-beingmentioning
confidence: 99%